TEKNIK BERMAIN PERAN UNTUK MENINGKATKAN REGULASI EMOSI SISWA SD - Rima Irmayanti (Journal of Innovative Counseling : Theory, Practice, and Research, 2017)
AbsractThis study raised from emotional problems in elementary students, where emotions their felt can not to be regulated. This seen from the behavior that their shown directly on someone who they did’nt like, such as: make fun of friend which led to fights and other behavior as a result of the negative emotions that they feel. Thus the necessary interventions that can assist students in managing their emotions, one way is by role-playing techniques. This study aims to obtain empirical facts about the effectiveness of role-playing techniques to improving emotion regulation elementary students. The quasi-experiment method is used in this reseach. Emotion regulation questionnaire was used to obtain research data. The study population was a fifth grade elementary school students of Laboratorium Percontohan UPI Bandung of the academic year 2014/2015. The results of this study indicate that the fifth grade elementary school children majority can regulate their emotion. Emotion regulation is consist of five aspects: situation selection, situation modification, attentional deployment, cognitive change, and response modulation. The students data pre-post test of emotion regulation were analyzed with quantitaive data. The results showed that students of emotion regulation after role-playing technique was implemented statistically changes better, which is a significant difference between the scores of pre and post test who obtained by students in the experimental group. In addition, compared to the control group, the experimental group has a significant change after the implementation of role-playing techniques.